The Effect of Product Innovation and Marketing Networks on Increased Micro Business Income - Upit Elya Rohimi; Widya Widya (Journal of Sharia Micro Enterprise and Cooperation, 2025)
Micro businesses have a vital role in supporting the national economy, but still face challenges in increasing income due to lack of product innovation and limited marketing networks. This study aims to analyze the effect of product innovation and marketing networks on increasing micro business income in Cirebon City. The method used is a quantitative approach with probability sampling technique, involving 65 respondents of micro business actors. Data analysis techniques include classical assumption test, multiple linear regression, coefficient of determination, as well as t test and F test. The results showed that both product innovation and marketing network had a positive and significant effect on micro business income, with a simultaneous contribution of 71.2%. The implications of these findings indicate the importance of a combination of innovative strategies and the expansion of marketing networks in driving the financial performance of micro enterprises. This research provides practical contributions for MSME actors as well as theoretical implications for strengthening the concept of innovation and marketing integration in the context of micro-entrepreneurship.